Analysis of Supply Chain Management on Audio System Product at CV. Cipta Mekar - lham, M.; Ludiya, Eka (Publisher Cv. Inara, 2024)
This study aims to analyze the supply chain management performance of audio system products at CV. Create Bloom. Another objective is to find out the material flow, information flow, and product flow run by CV. Cipta Mekar. The research method used is descriptive qualitative, using purposive sampling technique. Data collection techniques in this study were observation, interviews and documentation. In addition, performance assessment is carried out using the Scor Model. The results showed that the material flow did not run properly. The flow of information with a circular communication pattern and the simultaneous dissemination of information did not go well. In the product flow there is a shortage of stock and there is no quality control process. The results of the Scor Model show that the daily inventory performance is not good. In this case, there are still many things that need to be improved in the supply chain management of audio system products on CV. Cipta Mekar.